The determination of the displacement of the wooden construction materials under load via digital image processing - Tasci, Levent (Academic Journals, 2010)
Wood is used in the building sector, in the construction of gangways and bridges, scaffolds, groundworks, building conveying systems, and in the production of the constructional components such as roofs and walls because of a diverse range of its features such as its tractablity, natural outlook, lightness and being a heat-insulator. Wooden buildings are lighter and more durable than the buildings constructed with other techniques. Earthquake security is fully ensured in the buildings constructed with the wooden framing technology. This paper aims to determine and compare the displacements of plane tree resulting from the three point bending test by using image processing based methods and comparators. It also examines the strength properties of the oven dried woods under different moisture values. An increase in the strength of the wood and a decrease in its elasticity was observed with the removal of the moisture in the wood.
Keywords: Wood; displacement; digital image processing